Comparison of English Comprehension among Students from Different Backgrounds using a Narrative-Centered Digital Game - Talandron-Felipe, May Marie P (Archīum Ateneo, 2021)
This paper reports the continuation of the field testing of a narrative-centered digital game for English comprehension called Learning Likha: Rangers to the Rescue (LLRR) with a two-fold goal: first, identify the differences in terms of usage, attitudes towards, and perceptions of the English language between students from southern Philippines and the National Capital Region, and second, to determine how the LLRR in-game performance, post-test comprehension scores, engagement, and motivation of students differ between the groups. The participants who are grade school students from a province in southern Philippines answered questionnaires about their attitude towards and perception of English, played LLRR, answered the English comprehension post-test, and assessed their engagement and motivation using the adapted game-based learning engagement (GBLE) and intrinsic motivation inventory (IMI) questionnaires, respectively. Responses and interaction logs were compared to the data collected from NCR. Findings showed no significant difference between the groups in terms of the usage of English whether at home or with friends. However, NCR-based students were more receptive in terms of their perception and attitude towards the language, had better LLRR in-game performance, and obtained higher English comprehension post-test ratings. These findings are consistent with the results of the Programme for International Students Assessment (PISA) in 2018 where students from the southern regions have lower English reading literacy compared to those from NCR. In terms of GBLE and IMI responses, the gap is consistent as self-reports of participants from the south indicated lower behavior and emotion engagement, enjoyment, effort exerted, and perceived competence while playing LLRR.